1994
DOI: 10.1267/ahc.27.527
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Histatin 5 in Salivary Gland Tumors.

Abstract: Histatin is a group of histidine-rich polypeptides specific to parotid and submandibular gland secretions with several different biological functions such as stabilization of mineral-solute interaction in oral fluid, and antibacterial and antifungal actions. The authors generated polyclonal antibody to histatin by using purified histatin 5 as an immunogen and assayed the immunoreactivity by enzyme linked immunosorbent assay (ELISA) and immunoblotting. The antibody was further used to localize histatin in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Later, researchers mainly followed the protocols of Baum et al (1977a), with some modifications (MacKay et al, 1984a;Oppenheim et al, 1988;Raj et al, 1990;Tsai et al, 1996). Because the "histatin" nomenclature was adopted by Oppenheim et al (1988) ed against chemically synthesized histatin-5 in rabbits (Shrestha et al, 1994 Lal et al, 1992c;see Table 2). Pollock's group determined that HRP-2 is the non-phosphorylated form of HRP-l or histatin-l (Lal et al, 1992c), and this agreed with the prediction of .…”
Section: (I) Introductionmentioning
confidence: 99%
“…Later, researchers mainly followed the protocols of Baum et al (1977a), with some modifications (MacKay et al, 1984a;Oppenheim et al, 1988;Raj et al, 1990;Tsai et al, 1996). Because the "histatin" nomenclature was adopted by Oppenheim et al (1988) ed against chemically synthesized histatin-5 in rabbits (Shrestha et al, 1994 Lal et al, 1992c;see Table 2). Pollock's group determined that HRP-2 is the non-phosphorylated form of HRP-l or histatin-l (Lal et al, 1992c), and this agreed with the prediction of .…”
Section: (I) Introductionmentioning
confidence: 99%
“…The immuno-histochemical expression of histatin 5 has also been investigated in detail, revealing that the duct cells of all salivary glands are stained intensely and that duct-like tumor cells and modified myoepithelial tumor cells or plasmacytoid cells in pleomorphic adenoma show positive reactivity to histatin. It is suggested that the precursor cells of salivary gland tumors secrete histatin protein (49).…”
Section: Histatinsmentioning
confidence: 99%